Development of journalism ethics: a comparative analysis of codes of ethics in Nigeria, United Kingdom, United States of America, India, and Russia - Topic Peremobowei Akoje; Mohd Helmi Abd Rahim (Universiti Kebangsaan Malaysian, 2014)
Journalism codes of ethics are developed to guide journalists through their day-to-day encounter with ethical dilemma in the course of discharging method to find the similarities and differences in codes of ethics as promulgated their duties. The codes and canons provide journalists a framework for self-monitoring and self-correction. This subset of media ethics is widely known to journalists as their professional “codes of ethics” or the “canons of journalism”. However, efforts by professional journalism bodies to come up with universally acceptable standards of codes of ethics is still suffering setback because most codes of ethics are rooted in the socio-cultural, religious and political milieu of the countries they emanated from. The researcher had used comparative by five countries under review. There are several common cognitions such as truth and accuracy that are central values in journalism ethical codes of the five countries despite the fact that they were built on diverse nations’ politics and cultures. However, the five nations possess different regulations, yet, the researcher attempts to interpret the advantages while ignoring the drawbacks from those mentioned countries’ codes for the purpose of developing a code of ethics to guide journalists to run their duty with universal values in the journalism practicing industry.